Pain interference and associated factors in young adults with juvenile idiopathic arthritis. (3rd September 2019) - Rebane, K; Orenius, T; Ristolainen, L; Relas, H; Kautiainen, H; Luosujärvi, R; Säilä, H; Aalto, K
Abstract : Objective : Pain is a common and distressing feature of juvenile idiopathic arthritis (JIA). Pain interference (PI) is underexplored in long-term conditions such as JIA. The aim of this study was to explore the factors associated with PI in young adults with JIA. Methods : All consecutive JIA patients aged 18–30 years in three tertiary rheumatology and rehabilitation centres in Finland between September 2015 and April 2016 were included. The patients completed questionnaires addressing demographics, disability, depressive symptoms, pain anxiety, pain intensity, and PI. PI was measured with a single item from the RAND-36 questionnaire. Five response categories were coded into three groups: patients reporting 'extremely', 'quite a bit' or 'moderate' were classified as having significant PI; 'a little bit' as having minor PI; and 'not at all' as having no PI. A leisure-time physical activity metabolic equivalent of task (LTPA MET) was calculated. Statistical comparisons between PI and categorical variables were made using chi-squared or Fisher–Freeman–Halton tests. Results : Of the total 195 patients, 97 (50%) patients reported PI. PI was associated with a wide spectrum of sociodemographic and disease-related variables. Pain intensity scores were higher in patients expressing greater PI (p < 0.001). Greater PI was associated with higher disability (p < 0.001), higher pain anxiety scores (p < 0.001), lower LTPA MET (p = 0.027), and poorer leisure-time activity (p < 0.001). Conclusions : PI is common in young adults with JIA. We suggest that PI should be taken into account in future outcome studies exploring the impact of pain in children and young adults with JIA.